Restoring Functions and Hope, the Role of Public Health/Community Medicine in Hand Burn Recovery - Sarah Zaka, Ghazala Yasmeen, Saleha Afridi, Samina Waseem, Sarfraz Ahmad, Saqib Ismail, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hand burns generate severe functional limitations that restrict people from doing their daily routines and affect their life quality. Parts of plastic surgery practice focus on restoring hand function via skin grafting in combination with flap reconstruction and contracture release procedures. The research assesses how plastic surgery enhances healing along with functional improvement and scar quality in patients burned on their hands. Methodology: The researchers conducted their study at Sheikh Zayed Hospital, Rahim Yar Khan for the duration of 12 months from June 2022 to June, 2023 with 128 participants who experienced second- and third-degree hand burns. The surgical treatments for patients included skin grafting and local flap procedures alongside contracture release methods according to burn extent. Examining functional recovery used the Michigan Hand Questionnaire (MHQ) and rating scar quality depended on the Vancouver Scar Scale (VSS) at different follow-up sessions particularly at 12 weeks and 12 months. All statistical procedures involved paired t-tests and ANOVA along with regression models operating at p values below 0.05. Results: The 12-week results showed that 94.5% of patients achieved full epithelialization which continued to provide functional enhancement until the 12-month evaluation. The MHQ scores demonstrated statistical improvement from 42.3 ± 9.6 to 81.7 ± 8.9 (p < 0.001) while VSS scores showed a similar pattern with results changing from 12.4 ± 3.1 to 4.3 ± 2.1 (p < 0.001). The functional outcomes from flap reconstruction procedures reached 85.6 ± 7.2 points (p < 0.01) with entirely successful results while patient age above 61, diabetes mellitus, and severe burn injury exacerbated negative outcomes (p < 0.01). Conclusion: The outcome of hand burn patients receiving plastic surgery improves their wound healing as well as their hand function and produces superior scarring results. More studies should examine both extended treatment results along with additional treatment options for patients. Keywords: Hand burns, plastic surgery, skin grafting, functional recovery, wound healing, reconstructive surgery.